Lung deformations and radiation‐induced regional lung collapse in patients treated with stereotactic body radiation therapy. Issue 11 (15th October 2015) - Diot, Quentin; Kavanagh, Brian; Vinogradskiy, Yevgeniy; Garg, Kavita; Gaspar, Laurie; Miften, Moyed
Abstract : Purpose: To differentiate radiation‐induced fibrosis from regional lung collapse outside of the high dose region in patients treated with stereotactic body radiation therapy (SBRT) for lung tumors. Methods: Lung deformation maps were computed from pre‐treatment and post‐treatment computed tomography (CT) scans using a point‐to‐point translation method. Fifty anatomical landmarks inside the lung (vessel or airway branches) were matched on planning and follow‐up scans for the computation process. Two methods using the deformation maps were developed to differentiate regional lung collapse from fibrosis: vector field and Jacobian methods. A total of 40 planning and follow‐ups CT scans were analyzed for 20 lung SBRT patients. Results: Regional lung collapse was detected in 15 patients (75%) using the vector field method, in ten patients (50%) using the Jacobian method, and in 12 patients (60%) by radiologists. In terms of sensitivity and specificity the Jacobian method performed better. Only weak correlations were observed between the dose to the proximal airways and the occurrence of regional lung collapse. Conclusions: The authors presented and evaluated two novel methods using anatomical lung deformations to investigate lung collapse and fibrosis caused by SBRT treatment. Differentiation of these distinct physiological mechanisms beyond what is usually labeled "fibrosis" is necessary for accurate modeling of lung SBRT‐induced injuries. With the help of better models, it becomes possible to expand the therapeutic benefits of SBRT to a larger population of lung patients with large or centrally located tumors that were previously considered ineligible.